Reliability Analysis Of Subsea Pipelines In High Wave Random Conditions - Firman Husain (Collaborate, 2023)
To fulfil human energy needs, offshore oil and gas exploration requires an efficient distribution method for oil and gas products. This is because the operating costs of offshore exploration activities are prohibitive. One of the most efficient distribution methods is using underwater pipes. However, in the system, many obstacles pose a risk to pipe safety during installation. Therefore, pipes need to be designed to remain safe during installation. The pipes that are laid fulfil their design objectives as oil and natural gas distribution lines—the standards used in the design process are DnV OS F101 and DnV RP E305. The design and installation analysis process carried out in this study is a pipe with a diameter of 32 inches on the SSWJ-PGN project phase 1 zone 5. The pipe is designed to deal with design environmental parameters in the form of wave height and significant wave period with a return period of one year for installation conditions and a return period of one hundred years for operating conditions. Installation analysis was carried out through modelling in three directions of wave arrival, namely 0°, 45° and 90°. Next, a simulation is carried out with random variables in the form of wave height and steel yield strength to determine the effect of this randomness on the total stress in the pipe during the installation process. The random wave height variable is generated through a stochastic approach, assuming the waves follow the Rayleigh distribution shape. The random variable steel yield strength is generated based on the Log Normal distribution form [1] with a coefficient mean of 1.05 and a coefficient of variation of 0.1. The simulation process was carried out with 100 units of random data each for three directions of wave arrival.